The Masquerade in the Marketplace: dele jegede's Introspections and Reflections In Colors and Lines - Toyin Falola (Yoruba Studies Review)
This essay is about the art and life of dele jegede, one of the foremost Yoruba artists and cartoonists. The essay argues that dele jegede's oeuvre is a mirror of his life experiences and journeys depicting contemporary conditions of lifestyles, economics, and politics that he has witnessed, the harsh conditions of life in Africa, and the consciousness of exile. A striking focus of dele jegede's art is on underdevelopment and its consequences, particularly on poverty, politics and policies of change, identity, and violence. The discussion is centered on the artist as a scholar; the artist-scholar in Africa (Nigeria); and the artist-scholar in the Diaspora (United States). In each of the tiers, dele jegede comes across variously as a committed artist, a spectator, an interrogator, an advocate, an environmentalist, and much more.